Risk factors for infant mortality in the working area of the community health center - Lailatul Khofiva; Nur Lu'lu Fitriyani; Rr. Vita Nurlatif; Nur Hilal (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Infant Mortality Rate (IMR) remains a key indicator of public health and health development. In 2024, Wonopringgo Primary Health Care recorded the highest infant mortality in Pekalongan Regency. Purpose: To identify risk factors associated with infant mortality in the Working Area of the Community Health Center Method: A quantitative case-control study was conducted. Data were analyzed using the chi-square test, Odds Ratio (OR), and 95% Confidence Interval (CI). The study population is all mothers who give birth to babies in the working area of the Wonopringgo Health Center. The research sample consisted of two groups, namely the case group (mothers who experienced infant deaths) and the control group (mothers with live babies). Sampling was carried out using the total sampling technique in the case group and a 1:1 ratio between cases and controls according to the inclusion and exclusion criteria that have been set. Results: Maternal education (p=0.000;OR=21.429),maternal employment (p=0.006; OR=5.950), gestational age (p=0.033; OR=3.852), Antenatal Care (ANC) visits (p=0.014; OR=4.911), maternal health history (p=0.035; OR=4.911), and travel time to health facilities (p=0.007; OR=5.714) were significantly associated with infant mortality. Conclusion: Infant mortality is influenced by maternal social factors, pregnancy conditions, health service utilization, and access to health facilities.